DRUG THERAPY OF CARDIOVASCULAR DISEASES: DATA OF EVIDENCE-BASED MEDICINE AND CLINICAL PRACTICE - R. G. Oganov; S. Y. Martsevich (Российский кардиологический журнал, 2001)
Drug therapy of cardiovascular diseases: data of evidence-based medicine and clinical practice.